Rape and Gender Conflict in a Patriarchal State - Johnson, Richard Ronald (Crime & delinquency, 2014)
The handling of rape by the criminal justice system may be intimately intertwined with the gender inequality found in patriarchal communities. The present study examined the empirical relationship between female sociopolitical power and the rape rates and rape case clearance rates of 105 counties in an agrarian state with a reputation for patriarchal culture. The results suggested that, after controlling for contextual variables, counties with higher levels of female sociopolitical power also experienced higher rates of rape, and lower proportions of rape cases cleared by an arrest. The findings suggested that women in patriarchal communities experience a backlash effect as they achieve progress toward gender equality.